A farmer's guide to citrus production - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
This guide is neither a literature review nor does it seek to achieve the status of a technical paper. Instead, it attempts to be as current as possible with the understanding that changes are currently occurring especially in the fields of environment-friendly pesticides, wider ranges of inorganic fertilizer, and varying management styles and strategies as they all relate to citrus production. Indeed, not all aspects are addressed. The challenge lies for the farmer and interested parties to use this guide with the technology available to advance in awareness and knowledge of citrus.